Expanding the scope of N-heterocyclic carbene-organocatalyzed ring-opening polymerization of N-tosyl aziridines using functional and non-activated amine initiators. (October 2017) - Bakkali-Hassani, Camille; Rieger, Elisabeth; Vignolle, Joan; Wurm, Frederik R.; Carlotti, Stéphane; Taton, Daniel
Graphical abstract: Highlights: Polaziridines are synthesized by NHC-organocatalyzed ring-opening polymerization. Initiators include an allyl-functionalized N -activated amine, n -Bu2 NH, and N3 SiMe3 . Control over molar masses, dispersity and chain-ends is achieved. Polyaziridines with allyl and azido function are derivatized by "click chemistry". This provides novel possibilities for engineering polyaziridines in a simple way. Abstract: Polyaziridines (PAz) were synthesized for the first time by the 1, 3-bis(isopropyl)-4, 5(dimethyl)imidazol-2-ylidene-organocatalyzed ring-opening polymerization (OROP) of 2-alkyl- N - p -toluenesulfonyl aziridine (alkyl = methyl or phenyl), in the presence of both functional activated amine and non-functional non-activated amine initiators. Thus, not only an allyl-functionalized N -sulfonyl amine could serve as initiator, but also trimethylsilyl azide allowed introducing an allyl and an azido functionality in α-position of PAz chains, respectively. A non-activated and commercially available secondary amine, such as di- n -butylamine, also effectively initiated the OROP of N -tosylaziridines. Excellent control over molar masses, high chain-end fidelity and narrow dispersities ( Ð ≤ 1.20) were achieved, as attested by NMR spectroscopy, size exclusion chromatography and MALDI ToF mass spectrometry. PAz precursors consisting of the alkene or the azido functionality could further be derivatized, highlighting the accessibility of those functional groups. Overall, this N -heterocyclic carbene-OROP methodology offers a metal-free route to well-defined α-functionalized PAz.